Effects of continuous exposure to total dissolved gas supersaturation on swimming ability and recovery in grass carp (Ctenopharyngodon idella). Issue 2 (25th October 2021) - Cao, Chenyang; Fan, Zequn; Wang, Yuanming; Liu, Xiaoqing; Shi, Haoran; Yang, Yao
Abstract: Total dissolved gas (TDG) supersaturation caused by flood discharge water is becoming a serious environmental problem that threatens the survival of fish. The swimming ability of fish may be influenced by TDG supersaturation. To investigate the effects of continuous exposure to TDG supersaturation on fish swimming ability, we measured the critical swimming speed ( U crit ) and burst swimming speed ( U burst ) of grass carp continuously exposed to TDG supersaturation. The U crit values of grass carp were 6.34–3.68 body length per second (BL/s) at 100%, 105%, 110%, 115%, 120%, 125%, 130% and 135% TDG, while the U burst values were 10.2–8.96 BL/s at these TDG levels. The swimming ability ( U crit and U burst ) of grass carp decreased with increasing TDG levels and was significantly decreased at higher TDG levels (>120%). A swimming ability recovery test was used to investigate the effects of recovery on the swimming ability of grass carp continuously exposed to TDG supersaturation. When grass carp experienced exposures of 115%, 120%, 125%, 130% and 135% TDG, the recovery ratios of U crit were 76%–82% and 77%–86% after recovering for 1 and 2 h, respectively, in freshwater (100% TDG). The recovery ratios of U burst of grass carp were 84%–98% and 95%–97% under the same recovery conditions and TDG levels. The results showed that the recovery ratios of both U crit and U burst increased with the extension of the recovery time. The swimming ability of grass carp provided with a 2‐h recovery time recovered almost completely.